Perceived effectiveness of 'Zon Bebas Asap Rokok Melaka' towards universities students in Bandar Melaka / Rosilawati Sultan Mohideen, Wan Azfarozza Wan Athmar and Siti Faidul Maisarah Abdullah - Sultan Mohideen, Rosilawati; Wan Athmar, Wan Azfarozza; Abdullah, Siti Faidul Maisarah (Research Management Institute (RMI), 2012)
More than 10,000 Malaysians die from smoking-related illnesses every year. It stated that 30% of those above the age of 30 suffer from up to 40 kinds of illnesses which include heart problems and 57 types of cancer. Statistics show that every day about 50 teenagers below the age of 18 start smoking and most of them become hardcore smokers. However, the Malaysian government has taken a proactive approach in dealing with this problem and in order to curb smoking in Malaysia, the government launched a nationwide anti-smoking campaign in 2004, Tak Nak Merokok'. The main objective of the programme is to train health professionals, starting with pharmacists, to help smokers quit by using behavioural and pharmacological approaches. Its' target is on the younger generation (Syaza Dzulkifli, 2010). The objectives of this research are to identify the awareness among university students on 'Melaka Bebas Asap Rokok' campaign and also to determine their responses towards it. It is also to study the effects of that campaign towards them. Quantitative research will be used for this research and questionnaire will be distributed to the university students. Data will be analysed by using SPSS and there will be pre-test to test the validity and reliability. 'Melaka Bebas Asap Rokok' is one of the state level antismoking campaigns which is hoped to prevent smokers from smoking in public places which can lead to the decrease of numbers of smokers in Melaka. Despite banners and media coverage of the anti-smoking campaign, the result have yet been seen.